Turning Points in the Expansion of Christianity : from Pentecost to the present - Ott, Alice T. (Grand Rapids, Michigan : BakerAcademic, 2021)
"This book tells the story of pivotal turning points in the expansion of Christianity, enabling readers to grasp the big picture of missional trends and critical developments"--
Includes bibliographical references (p. 279-287) and index.
Keywords: Missions -- History; Church history